2017
DOI: 10.1051/matecconf/201710102016
|View full text |Cite
|
Sign up to set email alerts
|

The effect of enzymatic pretreatment and c/n ratio to biogas production from rice husk waste during solid state anaerobic digestion (SS-AD)

Abstract: Abstract. Rice husk is one of agricultural waste generated from the mill is potential to be converted to biogas. Otherwise, biogas production facing problem due to the high lignin content. This research is objected to study the effect of enzymatic pretreatment and C/N ratio to biogas production from rice husk by solid state anaerobic digestion (SS-AD). The laboratory scale-anaerobic digestions was used in this work. It is operated in batch system and with room temperature. Total solid (TS) was set 21%. Enzymat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…(Taherdanak & Zilouei, 2014) also found that lignin and hemicellulose in wheat plants were reduced using 8% NaOH. Recent research was also conducted by (Syafrudin, Dwi Nugraha, Hawali Abdul Matin, & Budiyono, 2017) where the addition of 3% NaOH for 24 hours can increase biogas production from rice husks under 21% TS conditions and a C/N ratio of 25. So it can be stated that chemical treatment with NaOH gives influence on biogas production compared without treatment with NaOH in an L-AD or SS-AD atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…(Taherdanak & Zilouei, 2014) also found that lignin and hemicellulose in wheat plants were reduced using 8% NaOH. Recent research was also conducted by (Syafrudin, Dwi Nugraha, Hawali Abdul Matin, & Budiyono, 2017) where the addition of 3% NaOH for 24 hours can increase biogas production from rice husks under 21% TS conditions and a C/N ratio of 25. So it can be stated that chemical treatment with NaOH gives influence on biogas production compared without treatment with NaOH in an L-AD or SS-AD atmosphere.…”
Section: Resultsmentioning
confidence: 99%
“…The preliminary treatment in this research with rice husk raw material aims to improve the optimization of rice husks up to 30% [5]. The result of analysis TS content is 93,4% of total solid.…”
Section: Preliminary Treatment and Solid Anaerobic Digestionmentioning
confidence: 99%
“…However, the smallest biogas production is in the 18 mesh reactor, which produces a total biogas yield of 960. 5…”
Section: Effect Of Grinding Size Variationsmentioning
confidence: 99%
“…With the addition of Na 2 CO 3 and the hydrolysis of polysaccharides is expected to produce a lot of biogas in a short time. Similar with tapioca, many researchers have conducted research on biogas from waste such as agricultural waste is able to produce a lot of gas through an anaerobic process [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%